From conflict to recovery in Africa - Addison, Tony.; World Institute for Development Economics Research (Oxford ; New York : Oxford University Press, 2003)
War has destroyed the hopes and lives of millions of Africans. How can we help Africa's communities to recover? How can we ensure that recovery from conflict benefits the poor and not just a narrow elite? These are just some of the vital questions asked and answered in this book, which examines recovery from conflict in Africa.
"A study prepared for the World Institute for Development Economics Research of the United Nations University (UNU/WIDER)."
Series statement on jacket.
oif 08/08/16
Loan
Keywords: Privatization; Economic policy; Africa, Sub-Saharan